PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA TENAGA KEPENDIDIKAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MODERATING - Hasan Hasan; Sri Wibawani (Jurnal Penelitian Administrasi Publik, 2019)
Organizational culture is a rule or norm that applies in an organization, as a form or way for each member to behave well towards the organization itself and with the tools or elements outside the organization in an effort to shape motivation in each employee in order to improve performance. Research results (1) Effect of Organizational Culture and Performance of Educational Personnel can be stated that there are real and significant influences; Organizational Culture and Work Motivation can be stated that there are real and significant influences. Based on the hypothesis test of Work Motivation and Performance of Educational Personnel it can be stated that there is a significant and significant influence, Organizational Culture on the Performance of Educational Personnel moderated by Work Motivation Variables and significant. (2) Correlation coefficient between Organizational Culture and Performance of Education Personnel has a very low low relationship, Correlation coefficient between Organizational Culture and Work Motivation there is a very Low relationship, Correlation coefficient between Work Motivation and Performance of Education Personnel is Low, and Correlation Coefficient between Organizational Culture of the Performance of Educational Personnel in Moderation of Work Motivation There is a Low relationship. (3) Effect of Organizational Culture on the Performance of Educational Personnel with Work Motivation as a moderating variable (Study of the Implementation of Apples and Morning Gymnastics in UPN "Veteran" East Java) is 7.7% which means that the influence of Organizational Culture variables and Work Motivation variables on Performance Education staff is 7.7%, while 92.3% is influenced by other factors outside the research model. Kеywords: Organizational Culture, Work Motivation, Employee Performance